PELAKSANAAN HALAQAH TAHFIDZ AL-QUR'AN SDIT BINA INSAN LUHUR KARTASURA SELAMA PANDEMI COVID-19 - Fetcha Shofani Firdaus; M. Muhroji (Universitas Muria Kudus, 2022)
The aims of this study were to describe, identify, and examine: 1) The principles of implementing Al-Qur'an halaqah tahfidz activities at SDIT Bina Insan Luhur Kartasura; 2) The benefits of carrying out halaqah tahfidz Al-Qur'an activities at SDIT Bina Insan Luhur Kartasura; 3) Supporting factors and obstacles in carrying out Al-Qur'an halaqah tahfidz activities at SDIT Bina Insan Luhur Kartasura; and 4) Efforts to overcome obstacles in implementing Al-Qur'an halaqah tahfidz activities at SDIT Bina Insan Luhur Kartasura during the COVID-19 pandemic. The research method used is descriptive qualitative. Data collection techniques using observation techniques, interviews, and documentation. Triangulation test is used to test the validity of the data. The data analysis technique in this research is interactive analysis. The results showed that 1) The main principle of halaqah tahfidz Al-Qur'an activities at SDIT Bina Insan Luhur Kartasura is that students not only memorize the Al-Qur'an but also practice the contents contained in the Al-Qur'an. 2) The benefit of halaqah tahfidz Al-Qur'an activities at SDIT Bina Insan Luhur Kartasura is to shape the morals of students to become of noble character. 3) The factors that support halaqah tahfidz Al-Qur'an activities are student enthusiasm, support from parents, adequate supporting teachers, and a supportive community. Obstacles to halaqah tahfidz Al-Qur'an activities are the lack of enthusiasm of students, lack of parental support, teachers who are not optimal in teaching, peer influence. 4) Efforts to overcome supporting teachers motivating students, supporting teachers motivating parents, principals motivating supporting teachers.